Additional cytogenetic abnormalities in resource constraint countries; an additional burden on Chronic Myeloid Leukemia patients ? - ANWER, DR. NIDA; FATIMA, NAVEENA; KHURRAM, SANA; SHAMSI, TAHIR (LIAQUAT MEDICAL RESEARCH JOURNAL, 2021)
The objective of this study was to analyze the additional cytogenetic abnormalities at baseline in chronic myeloid (CML) leukemia patients, compare its characteristics with the patients having normal karyotype and to identify the rationale of performing cytogenetics in naive CML patients. A case control study was conducted, 18 cases and 36 controls were recruited from 2010-2018. Controls were diagnosed CML patients without additional cytogenetic abnormalities. SPSS was used to analyze the data, chi square and independent sample t- test was applied to observe the association. Kaplan -Meier was used to observe the survival outcomes. At follow up, after the initiation of treatment, there was no difference in cases and controls with respect to the hemoglobin, total leucocyte and platelet count. Molecular response at 06 month was similar between two groups while at 12 months there was a significant difference and controls were found to have higher response rate. Survival outcomes were also found same in cases and controls. Our findings reflect the negligible difference in clinical and molecular responses between cases and controls in CML patients. Thus, performing cytogenetics at baseline might not be helpful to predict progression of disease and treatment outcome.